Pemanfaatan Media Interactive Flat Panel dalam Pembelajaran PAUD untuk Perkembangan Sosial-Emosional dan Bahasa - Yayuk Istiana; Eka Danik Prahastiwi (YASIN, 2026)
The use of digital technology in early childhood education is increasingly important, but its use needs to be adapted to children’s developmental needs and characteristics. This study aims to analyze the use of Interactive Flat Panel (IFP) in developing the language and socio-emotional abilities of children aged 4–6 years at KB Putra Mandiri, Pacitan. This study employed a qualitative approach with a case study design, involving 17 children and 1 teacher as participants. Data were collected through observation, interviews, and documentation and were then analyzed using an interactive model. The results show a significant improvement in children’s development, with the socio-emotional aspect increasing from 40% to 85% and the language aspect increasing from 45% to 82%. Children showed improvements in sharing ability, empathy, communication, vocabulary development, and confidence in speaking. The use of IFP through interactive activities, such as educational games and digital stories, proved able to increase children’s engagement, participation, and learning motivation. These findings indicate that the appropriate use of technology can support children’s holistic development by integrating language and socio-emotional aspects simultaneously. The conclusion of the study emphasizes that IFP is effective in creating interactive and meaningful early childhood education learning. The implications of this study emphasize the important role of teachers in appropriately integrating technology to support early childhood development.